The outcome of a structures discharge plan on the level of knowledge and skills on both insulin administration and foot care in type II diabetes mellitus patients in a tertiary government hospital - Baking, Katrina Joyce; Elarmo, Hosanna; Estalilla, Aileta Gail; Rivera, Diana Alexis; Sanchez, Frances Joyce; Torres, Marian
A five day protocol, including pre-tests and post-tests and the implementation of a structured discharge plan focused on the knowledge and skills on insulin administration and foot care, was utilized on 30 patients with Diabetes Mellitus Type II in 2 charity medical wards of a tertiary hospital. Fifteen patients were randomly selected as the control group and the other 15 patients were chosen as the study group. The objective of the study is to determine if there is a significant increase in the knowledge and skills on insulin administration and foot care after the implementation of the Structured Discharge Plan. Results show that there is a significant increase in the post test scores of the study group as compared to their pre-test scores in both the knowledge and skills on insulin administration and foot care. The mean difference between scores showed that T>1.761 at a= 0.05. For the control group, they did not receive Structured Discharge Plan and showed no significant changes in their pre-tests and post-tests scores. Mean differences between scores all showed -2.262<T<2.262 at a=0.05.